Answer :

Given LHS = sin-1 (2x - √ (1 – x2))


Let x = sin θ


= sin-1 (2sin θ √ (1 – sin2 θ))


We know that 1 – sin2 θ = cos2 θ


= sin-1 (2 sin θ cos θ)


= sin-1 (sin2 θ)


= 2θ


= 2 sin-1 x


= RHS


sin-1 (2x - √ (1 – x2)) = 2 sin-1 x


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

State True or FalMathematics - Exemplar

State True or FalMathematics - Exemplar

Fill in the blankMathematics - Exemplar

Fill in the blankMathematics - Exemplar

Find the principaRD Sharma - Volume 1

State True or FalMathematics - Exemplar

State True or FalMathematics - Exemplar